Documents Central State Historical Archives in Lviv as a Channel of Social Communication - Bilushchak, Tetyana (Видавництво Львівської політехніки, 2013)
The paper analyzes the archival documents of the Central State Historical Archives in Lviv as a channel of social communication. What is important for the analysis and study of military affairs, the medieval city of Lviv in the second half of the XIV–XVIII centuries. The paper presents a computerization of archives, which plays an important role in the archive as a structure of social communication, which will establish new facts in the history of the city.
Keywords: Central State Historical Archive in Lviv; archival documents; Channel Social Communications; documentary communication; computerization of archives